Connection of protein and amino acid content of forage and medium quality winter wheat varieties - Mezei, Zoltán; Pongrácznl Barancsi, Ágnes; Sipos, Péter; Győri, Zoltán; Csapó, János (Acta Agraria Debreceniensis, 2009)
We analysed the crude protein content, amino acid content, amino acid composition of four forage and milling III. quality winter wheat varieties (Magor, Hunor, Róna and Kondor) from their samples from five following years (2003, 2004, 2005, 2006, 2007). We found that quantity of essential and non-essential amino acids rose with increase in crude protein content. On examination of protein amino acid composition in relation to crude protein content we found that the crude protein content increased the quantities of the non-essential amino acids also rose, while those of the essential amino acids decreased as the lysine, the limiting amino acid of wheat. We also established that, as crude protein content increased, the biological value of the protein decreased.